Effects of sports experience on children's gross motor coordination level - Biino, Valentina; Giustino, Valerio; Gallotta, Maria Chiara; Bellafiore, Marianna; Battaglia, Giuseppe; Lanza, Massimo; Baldari, Carlo; Giuriato, Matteo; Figlioli, Flavia; Guidetti, Laura; Schena, Federico (Frontiers in Sports and Active Living, 2023)
Background: Gross motor coordination (GMC) development could be influenced by age, gender, weight status, geographical area, living setting, home environment, socio-economic status, sports practice.Purpose: To verify whether practicing sports and practicing different sports could influence children's GMC level.: A total of 295 children aged 8-11 years were involved in the study and divided into 5 groups in relation to the sport they practiced: gymnastics group (n=67; 51F, 16M), cycling group (n=64; 15F, 49M), athletics group (n=47; 22F, 25M), swimming group (n=35; 20F, 15M), control group (n=82; 42F, 40M). The four subtests of the Körperkoordinations Test für Kinder (KTK) assessed children's GMC level. The scores from each of the four subtests were summed into the KTK total raw score (RS) and then converted into a gender-and age-specific motor quotient (MQ). Results: Children practicing sports showed significantly higher RS and MQ score than children of control group (203.14±38.55 vs 163.63±43.50 and 98.56±15.79 vs 83.01±16.71, respectively; p<0.001). Children practicing gymnastics had a significantly higher RS and MQ than children of cycling, swimming, and control groups (p<0.05), children of control group had a significantly lower RS and MQ than children of all other groups (p<0.05). Children practicing gymnastics performed better walking backwards subtest than all other children's groups (p<0.001). Children of control group performed worse jumping sideways subtest than children of gymnastics, athletics and swimming groups (p<0.01). Children practicing gymnastics performed better moving sideways subtest than children of athletics, cycling and control groups (p<0.01); children of control group performed worse than children of all other groups (p<0.01). Children of control group performed worse hopping for height subtest than children of gymnastics, athletics and cycling groups (p<0.05); children practicing gymnastics performed better than children of swimming and control groups (p<0.05). Conclusions: The performance model and therefore the specialized training that each sport discipline required, could justified the differences in children's GMC level among sports groups. Thus, coaches should plan individualized interventions and choose activity contents to support children's GMC development.